Efficiency Test Of Colimator Shutter At The X Ray Tube In Radiodiagnostic Laboratory Of Poltekkes Jakarta 2 And Two Clinical Hospitals In Jakarta - Gando Sari; Gita Putri Wahyuni (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
The purpose of this study was to determine the efficiency of the collimator shutter with the presence or absence of leakage from the collector slit of the x-ray equipment. The type of research used is qualitative method using descriptive cross sectional method, conducting collimatory slot testing against x-ray equipment in laboratory and two installation of Radiology field of clinical practice for student of Radiodiagnostic and Radiotherapy of PoltekkesKemenkes Jakarta II. Result, there was a leakage of collimation shutter with marked blackening on x-rayfilm, on 8 (eight) x-ray equipment, there was a full leakage (very significant), and there was a big leak, and there was a slight leakage. Conclusion, in this research there is one x-ray equipment according to the standard reference (golden standard), set by Permenkes No. 1250 / Menkes / SK / XII / 2009 that is SH x-ray equipment in Y hospital.